PRODUKSI BENIH PADI HIBRIDA: KEMAJUAN, TANTANGAN, DAN PELUANG PENGEMBANGAN DI INDONESIA / Hybrid Rice Seed Production: Progress, Constraints, and Development Opportunities in Indonesia - Yuni Widyastuti; R. Noviadi Prabowo; Bayu P. Wibowo; Nita Kartina; Indrastuti A. Rumanti; Nurwulan Agustiani; Indria W. Mulsanti (Jurnal Penelitian dan Pengembangan Pertanian, 2022)
Hybrid seed production is the important key in the commercialization and development of hybrid rice. The successful of hybrid rice development through the exploitation of heterosis phenomenon in China encouraged other countries including Indonesia to develop hybrid rice. Research conducted at Indonesian Center for Rice Research (ICRR) indicated that the development of hybrid rice technology offered opportunities for increasing rice yields by 15-20% compared to inbred varieties. The high cost of hybrid seed is one of the constraints in the adoption of hybrid rice technology. This is primarily attributed to the low hybrid seed yield which is around 1-1.5 t/ha. This article introduces the results of research and development especially in hybrid rice seed production based on genetic of parental lines of hybrid and its field management. The constraints and opportunities of hybrid seed industry in Indonesia also discussed in this article.Keywords: Hybrid rice, seed production, progress, constraint, opportunity. AbstrakProduksi benih merupakan kunci penting dalam keberhasilan komersialisasi dan pengembangan padi hibrida. Keberhasilan Cina mengembangkan padi hibrida dengan memanfaatkan fenomena vigor hibrida (heterosis) telah mendorong negara lain termasuk Indonesia untuk mengembangkannya. Hasil Penelitian di Balai Besar Penelitian Tanaman Padi (BB Padi) menunjukkan penggunaan teknologi padi hibrida memberikan peluang peningkatan hasil 15-20% dibandingkan dengan varietas inbrida. Harga benih yang tinggi menjadi salah satu tantangan dalam adopsi padi hibrida. Hal ini disebabkan oleh produksi benih F1 yang hanya berkisar 1-1,5 t/ha. Artikel ini memaparkan hasil penelitian produksi benih padi hibrida, terutama berdasarkan genetik galur tetua hibrida dan teknis budidaya. Kendala dan peluang industri benih padi hibrida, strategi pengembangan produksi benih dan pembangunan industri benih padi hibrida di Indonesia juga merupakan bagian dari diskusi penting dalam artikel ini.Kata kunci: Padi hibrida, produksi benih, kemajuan, tantangan, pengembangan